Effect of propolis oral intake on physiological condition of young worker honey bees, apis mellifera L. - Damiani, Natalia (2017)
Honey bees collect resin from various plant species and transform it into propolis that is incorporated into the nest. The role of resins in the bee health field is poorly understood. The aim was to evaluate the effects of forced consumption of propolis on the physiological condition and short-term survival of Apis mellifera worker bees. It was tested if the number of circulating hemocytes in hemolymph, the abdominal fat bodies and the hypopharyngeal glands development were affected by the feeding with propolis extracts in laboratory conditions during the warm and the cold seasons. Propolis added to sugar candy was consumed by workers for fourteen days without affecting the bee survival. The number of circulating hemocytes in hemolymph remained constant despite the differential diet during the experiment. However, the development of fat bodies and hypopharyngeal glands was altered by propolis ingestion. The abdominal fat body development in winter bees diminished after fourteen days of propolis consumption, while it increased in summer bees. The hypopharyngeal gland development decreased for the assayed period in workers from both seasons. Our results encourage us to continue exploring this research field and learn how long-term forced ingestion of a plant-derived compound, a non-nutritive substance, can modify physiological bee parameters. A broader understanding of the multiple roles of propolis in the health of the honey bee colonies could be obtained by studying the ways in which it is processed and metabolized and the effect that generates in another physiological responses.